Composition of wet deposition in Kaynarca, Turkey - (:unkn) unknown (ELSEVIER SCI LTD, 2002)
In this work, composition of wet deposition in Kaynarca, Turkey is studied by collecting precipitation samples during more than a 2-year period, August 1993 November 1995. Concentrations of the main cations Na+, Mg2+, Ca2+, K+, NH4+ and the main anions Cl-, NO3- and SO42- together with pH were studied. The average pH value at Kaynarca was near neutral, 5.59. Results indicated that SO42 concentration in precipitation was very high, as was Ca2+, neutralizing the acidity. Acidic wet deposition samples were generally obtained in winter. Enrichment factors for sea and soil indicate the strong effects of sea and soil, specifically limestone on the composition of precipitation. Non-sea salt fractions of SO42- were found to range from 0.955 to 0.980, showing the effect of non-sea sources, especially emissions from fossil-fuel combustion, on the pH of samples. Trajectory analysis showed that cyclones originating from northwestern, central and eastern parts of Europe have generally high sulfate and nitrate concentrations and low pH. (C) 2002 Published by Elsevier Science Ltd.
Keywords: acid precipitation; wet deposition; neutralization; air pollution; trajectory analysis; PRECIPITATION; ISTANBUL